HIGH-PRESSURE EXPERIMENTAL GROWTH OF DIAMOND USING C-K2CO3-KCL AS AN ANALOGUE FOR CL-BEARING CARBONATE FLUID - Tomlinson E.; Jones A.; Milledge J. (My University, 2004)
High-pressure, high-temperature diamond growth experiments have been conducted in the system C–K2CO3–KCl at 1050–1420 °C, 7.0–7.7 GPa. KCl is of interest because of the strong effect of halogens on the phase relations of carbonate-rich systems [Geophys. Res. Lett. 30 (2003) 1022] and because of the occurrence of KCl coexisting with alkali silicate–carbonate fluids in natural-coated diamond [Geochim. Cosmochim. Acta 64 (2000) 717]. We have used system C–K2CO3–KCl as an analogue for these mantle fluids in diamond growth experiments. The presence of KCl reduces the potassium carbonate liquidus to ≤1000 °C at 7.7 GPa, allowing it to act as a solvent catalyst for diamond growth at temperatures below the continental geotherm. This is a reduction on the minimum diamond growth temperature reported in the alkali-carbonate–C–O–H system [Lithos 60 (2002) 145]. Diamond growth using carbonate solvent catalysts is characterised by a relatively long induction period. However, the addition of KCl also reduced the period for diamond growth in carbonate to 5 min; no such induction period appears to be necessary. It is suggested that KCl destabilises carbonate, allowing greater solubility and diffusion of carbon.
Keywords: High experiments; Diamond growth; Potassium carbonate; Potassium chloride